Julián Ríos, host at "Casa Ulises" - Viñas Piquer, David (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This article is presented as an analysis of the original way of proceeding that Julián Ríos follows to offer a literary journey through Joyce’s Ulysses in Casa Ulises, a hybrid work, located halfway between fiction and essay, which stands out not only by erudition of its author, but also by his ability to create clever puns and brilliant linguistic associations.